Snail and millipede complementarity in decomposing Mediterranean forest leaf litter mixtures (Functional Ecology, 2010)
1. The projected increase in loss of biodiversity worldwide has prompted the need to understand the role that diversity plays in key ecosystem functions such as litter decomposition and nutrient cycling. Here we asked how two contrasting species of saprophagous macrofauna and four Mediterranean forest leaf litter species interactively affect decomposition in a 6-week microcosm study. 2. Litter mass loss and macrofauna relative consumption rates (RCR) were measured on treatments with freshly fallen or partially decomposed leaf litter of Alnus glutinosa, Fraxinus angustifolia, Pistacia terebinthus and Quercus ilex as single-species or mixtures in absence and presence of the gastropod, Pomatias elegans, the diplopod, Glomeris marginata, or both macrofauna species. 3. Macrofauna consumed all litter substrates except freshly fallen P. terebinthus as a single-species litter that was fatal to both animals, although its presence in litter mixtures increased overall RCR. Consumption was higher in partially decomposed than freshly fallen litter, and higher in litter mixtures than in single-species litter. Both litter state and mixing interacted significantly with macrofauna treatment where generally, RCR by P. elegans alone was inferior to that of G. marginata alone or in combination with P. elegans. 4. An overall positive complementarity effect on litter RCR between G. marginata and P. elegans was observed in freshly fallen litter. Particularly strong complementarity was observed in two mixtures of freshly fallen litter and also in one mixture of partially decomposed litter. 5. There were no non-additive effects of litter mixing on litter mass loss in the absence of animals, indicating no interactions among litter substrates during decomposition. However, in the presence of either G. marginata and/or P. elegans, positive and negative interactions among litter substrates occurred and were enhanced or reversed by the addition of the second macrofauna species. 6. We conclude that saprophagous macrofauna play a critical role in the decomposition dynamics of Mediterranean forest litter by interacting with each other and by driving interactions among litter substrates.

Snail and millipede complementarity in decomposing Mediterranean forest leaf litter mixtures - De Oliveira, Tatiana; Hättenschwiler, Stephan; Tanya Handa, Ira (Functional Ecology, 2010)
1. The projected increase in loss of biodiversity worldwide has prompted the need to understand the role that diversity plays in key ecosystem functions such as litter decomposition and nutrient cycling. Here we asked how two contrasting species of saprophagous macrofauna and four Mediterranean forest leaf litter species interactively affect decomposition in a 6-week microcosm study. 2. Litter mass loss and macrofauna relative consumption rates (RCR) were measured on treatments with freshly fallen or partially decomposed leaf litter of Alnus glutinosa, Fraxinus angustifolia, Pistacia terebinthus and Quercus ilex as single-species or mixtures in absence and presence of the gastropod, Pomatias elegans, the diplopod, Glomeris marginata, or both macrofauna species. 3. Macrofauna consumed all litter substrates except freshly fallen P. terebinthus as a single-species litter that was fatal to both animals, although its presence in litter mixtures increased overall RCR. Consumption was higher in partially decomposed than freshly fallen litter, and higher in litter mixtures than in single-species litter. Both litter state and mixing interacted significantly with macrofauna treatment where generally, RCR by P. elegans alone was inferior to that of G. marginata alone or in combination with P. elegans. 4. An overall positive complementarity effect on litter RCR between G. marginata and P. elegans was observed in freshly fallen litter. Particularly strong complementarity was observed in two mixtures of freshly fallen litter and also in one mixture of partially decomposed litter. 5. There were no non-additive effects of litter mixing on litter mass loss in the absence of animals, indicating no interactions among litter substrates during decomposition. However, in the presence of either G. marginata and/or P. elegans, positive and negative interactions among litter substrates occurred and were enhanced or reversed by the addition of the second macrofauna species. 6. We conclude that saprophagous macrofauna play a critical role in the decomposition dynamics of Mediterranean forest litter by interacting with each other and by driving interactions among litter substrates.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Biodiversity; diplopod; gastropod; litter consumption; non-additive effects; synergy

The fate of condensed tannins during litter consumption by soil animals - Coulis, Mathieu; Hättenschwiler, Stephan; Rapior, Sylvie; Coq, Sylvain (Soil Biology and Biochemistry, 2009)
Condensed tannins (CT) can strongly affect litter decomposition, but their fate during the decomposition process, in particular as inﬂuenced by detritivore consumption, is not well understood. We tested the hypothesis that litter CT are reduced by the gut passage of two functionally distinct detritivores of Mediterranean forests, the millipede Glomeris marginata, and the land snail Pomatias elegans, as a ﬁxed proportion of initial litter CT, but more so in Pomatias since snails are known to have a more efﬁcient enzymatic capacity. Contrary to our hypothesis, both detritivore species reduced litter CT to near zero in their faecal pellets irrespective of the wide range in initial leaf litter CT concentrations of 9–188 mg g 1 d m among three Mediterranean tree species (Pistacia terebinthus, Quercus ilex, Alnus glutinosa) and different decomposition stages of their litter. The almost complete disappearance of CT even from some litter types highly concentrated in CT, due to either degradation by gut microorganism or complexation of CT into insoluble high molecular weight structures, suggests a high ‘‘de-tanning’’ efﬁciency across functionally distinct detritivore species. The transformation of CT-rich litter into virtually CT-free faecal pellets by detritivores might be highly relevant for the subsequent decomposition process in ecosystems with a high macrofauna abundance and CT-rich plant species such as Mediterranean forests.
Keywords: decomposition; Glomeris marginata; Macrofauna; mediterranean forest; polyphenols; Pomatias elegans; Tree leaf litter

The fate of condensed tannins during litter consumption by soil animals (Soil Biology and Biochemistry, 2009)
Condensed tannins (CT) can strongly affect litter decomposition, but their fate during the decomposition process, in particular as inﬂuenced by detritivore consumption, is not well understood. We tested the hypothesis that litter CT are reduced by the gut passage of two functionally distinct detritivores of Mediterranean forests, the millipede Glomeris marginata, and the land snail Pomatias elegans, as a ﬁxed proportion of initial litter CT, but more so in Pomatias since snails are known to have a more efﬁcient enzymatic capacity. Contrary to our hypothesis, both detritivore species reduced litter CT to near zero in their faecal pellets irrespective of the wide range in initial leaf litter CT concentrations of 9–188 mg g 1 d m among three Mediterranean tree species (Pistacia terebinthus, Quercus ilex, Alnus glutinosa) and different decomposition stages of their litter. The almost complete disappearance of CT even from some litter types highly concentrated in CT, due to either degradation by gut microorganism or complexation of CT into insoluble high molecular weight structures, suggests a high ‘‘de-tanning’’ efﬁciency across functionally distinct detritivore species. The transformation of CT-rich litter into virtually CT-free faecal pellets by detritivores might be highly relevant for the subsequent decomposition process in ecosystems with a high macrofauna abundance and CT-rich plant species such as Mediterranean forests.